2018
DOI: 10.1242/jeb.174623
|View full text |Cite
|
Sign up to set email alerts
|

Stress and disease resilience differences related to emergence time for first feeding in farmed rainbow trout (Oncorhynchus mykiss)

Abstract: Salmonid individuals show a relatively high variability in the time required to abandon the gravel nest where they hatch, the so-called 'emergence time'. Different behavioral and physiological traits have been shown to be associated with emergence time in wild salmonids. In general, early- and late-emerging fish have traits resembling those of proactive and reactive stress coping styles, respectively. Proactive fish are considered to be more resilient to stress and probably to disease, so it was hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The only observed effect of the repeated stress protocol on the fish acute stress response was a smaller peak in the plasma levels of lactate, and this effect was independent of the diet. The same result was observed before in another study using a similar protocol (Gesto et al, 2018). The reduction in the lactate response to the stressor suggests a faster lactate clearance rate or a reduced behavioral response to the stressor, resulting in less strenuous exercise and in a lower oxygen debt (Milligan and Girard, 1993).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The only observed effect of the repeated stress protocol on the fish acute stress response was a smaller peak in the plasma levels of lactate, and this effect was independent of the diet. The same result was observed before in another study using a similar protocol (Gesto et al, 2018). The reduction in the lactate response to the stressor suggests a faster lactate clearance rate or a reduced behavioral response to the stressor, resulting in less strenuous exercise and in a lower oxygen debt (Milligan and Girard, 1993).…”
Section: Discussionsupporting
confidence: 84%
“…shown to be highly diverse in their ability to habituate to repeated stress depending on their emergence time (Gesto et al, 2018). That large diversity might explain the lack of differences in the current study, where fish were not selected by emergence time.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Even when a genetic link might exist between behavior and the physiological stress responses, it has been suggested that the plastic nature of vertebrate behavior and the different subjective environmental conditions can easily uncouple both aspects of coping styles [52]. In the same direction, it has been also suggested that the decoupling between HPI responsiveness and behavioral and life history traits usually associated to stress coping styles might be favored by the process of domestication [20,53,56].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the current study, we wanted to get some information to investigate the stress response of the fish at the level of the CNS. The serotonergic system is believed to be involved in the organization of the integrated stress response in vertebrates [51,[57][58][59], and the activity of serotonergic neurons has been show to increase consistently upon stress exposure in fish [51,56]. The ratio between 5-HIAA and serotonin is used as an indirect estimator of the serotonergic activity, since 5-HIAA is usually produced after degradation of part of the 5-HT released at the synaptic terminal [59,60].…”
Section: Accepted Manuscriptmentioning
confidence: 99%